2022
DOI: 10.1021/acsenvironau.2c00048
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of HONO Measurement May Affect the Accurate Diagnosis of Ozone Production Sensitivity

Abstract: Recently, deteriorating ozone (O3) pollution in China brought the precise diagnosis of O3 sensitive chemistry to the forefront. As a dominant precursor of OH radicals, atmospheric nitrous acid (HONO) plays an important role in O3 production. However, its measurement unavailability in many regions especially for second- and third-tier cities may lead to the misjudgment of the O3 sensitivity regime derived from observation-based models. Here, we systematically assess the potential impact of HONO on diagnosing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Gaseous HONO acts as the dominant primary precursor of OH radicals. Thus, observed HONO was also used to constrain the box model in the presence or absence of Cl 2 and ClNO 2 because the model performance is greatly improved when HONO is accounted for . The calculations of the ozone formation rate P (O 3 ) and ozone chemical loss rate L (O 3 ) referred to the report by Ma et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaseous HONO acts as the dominant primary precursor of OH radicals. Thus, observed HONO was also used to constrain the box model in the presence or absence of Cl 2 and ClNO 2 because the model performance is greatly improved when HONO is accounted for . The calculations of the ozone formation rate P (O 3 ) and ozone chemical loss rate L (O 3 ) referred to the report by Ma et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, observed HONO was also used to constrain the box model in the presence or absence of Cl 2 and ClNO 2 because the model performance is greatly improved when HONO is accounted for. 38 The calculations of the ozone formation rate P(O 3 ) and ozone chemical loss rate L(O 3 ) referred to the report by Ma et al (2022). 36 In this study, the reaction between Cl radicals and O 3 was also accounted for to calculate L(O 3 ).…”
Section: Observation-based Model Simulationmentioning
confidence: 99%
“…The chain reaction with O 3 production is initiated and accelerated by primary radical production [ P (RO x ), including O 3 photolysis and nitrous acid (HONO) photolysis] and propagated by the following radical cycling. ,, Recent studies have highlighted the importance of P (RO x ) in exacerbating O 3 pollution. In particular, Wang et al reported that O 3 formation in Eastern China is sensitive to P (RO x ), while Liu et al demonstrated the significant contribution of primary radical sources, particularly HONO, to daytime O 3 production in a high-O 3 city in the North China Plain (NCP). These two studies highlight the need to recognize primary radical sources and indicate the potential role of P (RO x ) reduction in mitigating O 3 pollution in addition to conventional strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Soil has been identified as an important source of N r . N r emissions from soil are controlled by available soil nitrogen content and edaphic conditions such as soil water content (SWC) and temperature. ,,,, The NCP region occupies a large area of cultivated land (∼0.3 × 10 6 km 2 ) that is regularly treated with intensive chemical nitrogen fertilizers and also receives extensive nitrogen deposition. , The high soil nitrogen content from both agricultural fertilizer input and deposition have led to large soil N r emissions in the summertime. These soil emissions are conventionally considered as biogenic sources, even though a large proportion of them are originally from anthropogenic agriculture activities. A number of studies estimated significant episodic surface ozone enhancement from soil NO x and/or HONO emissions by up to 8 ppbv. ,, Lu et al pointed out a competing effect between NO x emissions from fuel combustion and soil on ozone formation in the NCP region, suggesting that soil ozone contribution may vary with changes in NO x emissions from fuel combustion. However, the role of soil N r ozone production in the observed increasing trends in surface ozone in China has not been recognized.…”
Section: Introductionmentioning
confidence: 99%